Implantable loop recorders in patients with a structural or electrical heart disease: comparison of the clinical value in patients with and without a history of syncope. (24th May 2021) - Assaf, A; Sakhi, R; Michels, M; Roos-Hesselink, JW; Verhagen, JMA; Baghwandien, RE; Szili-Torok, T; Theuns, DAMJ; Yap, SC
Abstract: Funding Acknowledgements: Type of funding sources: None. Background Patients with structural and electrical heart disease are at increased risk for sudden cardiac death. Guidelines recommend the use of an implantable loop recorder (ILR) in symptomatic patients when symptoms are sporadic and suspected to be related to arrhythmias. In clinical practice, an ILR is mainly used in patients with unexplained syncope. Purpose To compare the clinical value of an ILR in patients with a heart disease and a history of syncope versus those with non-syncopal suspected arrhythmia-related symptoms. Methods In this observational single-center study we included symptomatic patients with structural or electrical heart disease who received an ILR. The primary endpoint was an actionable event which was defined as an arrhythmic event leading to a change in clinical management. The secondary endpoint was an event leading to implantation of a pacemaker or implantable cardioverter-defibrillator (ICD). Results A total of 120 patients (mean age 47 ± 17 years, 49% men) were included. Underlying disease substrate was inherited cardiomyopathy (31%), congenital heart disease (28%), channelopathy (23%), and other structural heart disease (18%).There were 43 patients with a history of syncope (group A) and 77 patients with non-syncopal symptoms (group B) such as palpitations, dizziness and/or near-syncope at baseline. During a median follow-up of 19 months (IQR 8-36), a primary endpoint was reached in 14 patients (33%) of group A, and in 28 patients (36%) of group B (logrank P = 0.54, Figure A). There was also no significant difference in the cumulative rate of cardiac device implantation between group A and B, 14% versus 10%, respectively (logrank P = 0.97, Figure B). Conclusion Our results show no differences in ILR yield in patients with structural or electrical heart disease who present with any suspected arrhythmia-related symptom, including those with non-syncopal symptoms.